2007
DOI: 10.1111/j.1365-2249.2006.03320.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and systemic administration of β-glucan protects against lipopolysaccharide-induced shock and organ injury in rats

Abstract: Summaryb-Glucans are glucose polymers with a variety of stimulatory effects on the immune system. The objective of this study was to determine the effect of prophylactic oral administration of soluble Saccharomyces cerevisiae-derived b-1,3/1,6-glucan (SBG) on the outcome of experimental endotoxaemia and shock-associated organ injury. Male Wistar rats were pretreated with SBG orally (SBGpo, 20 mg/kg/day) for 14 days, subcutaneously (SBGsc, 2 mg/kg/ day) for 3 days, or vehicle (placebo). Rats were anaesthetized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 36 publications
3
62
0
2
Order By: Relevance
“…Several studies have shown that β-glucan is very good at improving immunity, and glutamine has an important role in cell-mediated immunity and the integrity of the intestinal mucosa (Sandvik et al 2007, Santos et al 2014, Wang & Ellis 2014, Chaudhry et al 2016, Li et al 2006 . In this report, we demonstrate for the first time the benefits of their association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that β-glucan is very good at improving immunity, and glutamine has an important role in cell-mediated immunity and the integrity of the intestinal mucosa (Sandvik et al 2007, Santos et al 2014, Wang & Ellis 2014, Chaudhry et al 2016, Li et al 2006 . In this report, we demonstrate for the first time the benefits of their association.…”
Section: Discussionmentioning
confidence: 99%
“…After oral administration of β-glucans, it comes in contact with the mucosa of gastrointestinal tract and it stimulates the intestinal immune cells, including Peyer's patches, promoting the increased number of intraepithelial lymphocytes (Sandvik et al 2007, Volman et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…While some studies have demonstrated that oral BG administration decreased TNF-a level [28], others reported that the level did not change significantly [29,30]. BG also increased the levels of IL-1 [29]. However, there are also studies which indicate no significant difference in the production of inflammatory cytokines [30].…”
Section: Discussionmentioning
confidence: 85%
“…BG administration is thought to blunt the host inflammatory response to the damage by inhibiting cytokine activity [27]. While some studies have demonstrated that oral BG administration decreased TNF-a level [28], others reported that the level did not change significantly [29,30]. BG also increased the levels of IL-1 [29].…”
Section: Discussionmentioning
confidence: 92%
“…The immunological potency of beta-glucans also can be associated with their ability to activate leukocytes (Sandvik et al, 2007). It is assigned and dependent on the molecular mass, conformation, solubility and also the degree and position of its ramifications.…”
Section: Immunomodulatory Activity Of Betaglucansmentioning
confidence: 99%